PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA - Rini Rejeki Susilowati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
The torture that resulted in the death of the Helper / Domestic Worker (PRT) is a crime against humanity that can not be tolerated anymore, such a condition indicates that Domestic Helper has lost Autonomy and Ownership of him can even be caught in the status of a